NILAI-NILAI PADA PELAKSANAAN PROJEK PROFIL PELAJAR RAHMATAN LIL ‘ALAMIN KURIKULUM MERDEKA DI MAN KOTA BANJARMASIN - Jannah, Raudatul; Mizani, Hilmi; Muhdi, Muhdi; M. Ramli, M. Ramli (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2024)
This study aims to describe the values of the Rahmatan Lil Alamin Student Profile Project (PPRA) in the implementation of the Independent Curriculum at MAN Banjarmasin City. This type of research is field research, namely research by going directly to the research location to obtain information about the values in the implementation of the PPRA Independent Curriculum Project at MAN Banjarmasin City. This research is descriptive with a qualitative approach. The subjects of this study were the PPRA project coordinator teachers at MAN Banjarmasin City, while the objects of this study were the values of the PPRA project in the implementation of the independent curriculum at MAN Banjarmasin City. The data collection techniques used were observation, interviews and documentation. The analysis technique used the Miles and Huberman interactive analysis model which involved the steps; data collection, data reduction, data presentation, as well as conclusions and verification. The results of the study were values in the implementation of PPRA at MAN in Banjarmasin City, namely: citizenship and nationality values (muwaṭanah), deliberation (syūra), tolerance (tasāmuh); and dynamic and innovative (taṭawwur wa ibtikār). The four PPRA values are instilled through different projects between one MAN and another. The projects implemented are a traditional game in South Kalimantan called Badaku, collecting garbage that is made into a seat mat, and decorative flowers, traditional Banjar dance (Rudat) and Saman Dance from Aceh, Pancasila Democracy work title, making contemporary halal food, making infographics, making educational videos and bazaar projects